Student Satisfaction with The Use of Chat-GPT as A Learning Resource - Yassin, Abdulnassir; Bashir, Ashadi (Yayasan Pendidikan Dan Pengembangan Harapan Ananda, 2024)
This study investigates student satisfaction with the use of Chat-GPT as a learning resource in higher education. This study used a mixed methods approach, combining quantitative surveys and qualitative interviews to assess students' experiences and perceptions. A sample of 200 students from various disciplines at the Faculty of Education, Islamic University in Uganda (IUIU) participated in the study. Findings showed that most students expressed a high level of satisfaction with Chat-GPT, citing the availability, responsiveness and quality of information provided as key benefits. However, there were concerns about the accuracy of some responses and the lack of personalized feedback. The study concludes that while Chat-GPT serves as a valuable complementary resource, it must be properly integrated into the broader educational context, to ensure complementary human guidance and verification. These insights are critical for educators and developers looking to improve the effectiveness of AI-based educational tools.